A Reformed Islamic Education: Grounds for Re-visiting Cosmopolitanism - Davids, Nuraan (South African Journal of Higher Education, 2016)
Inasmuch as Muslims and Muslim women in particular, are struggling to find accommodation and expression in a pluralist society, cosmopolitanism is grappling in its understanding and acceptance of what constitutes the presentations and representations of Muslim women. By proposing a reformed approach to Islamic education as well as a renewed cosmopolitanism, this article sets out to show how cosmopolitanism can contribute to the lived experiences of Muslim women, and how the latter can indeed find a space of recognised articulation. It is the main argument of this article that by re-visiting the notion of the otherness of Other, in terms of cosmopolitanism, and by exploring options for a reformed Islamic education - by specifically looking at the elements of ta’lim (instruction), ta’dib (just action) and tarbiyah (nurturing) - the nurturing of a commensurable relationship is not only possible, but holds unexplored implications for democratic citizenship education.